High-speed rail as a new mode of intercity passenger transportation - Eugene Chao; Vukan R. Vuchic; Aleksandr Vashchukov (Asian Development Bank Institute (ADBI), 2019)
High-speed rail is a new mode of intercity passenger transportation. The article reviews the history of the United States' (US) HSR development and makes a comparison with peer countries' HSR development. With the rapid progress of HSR and the successful competition with cars and air travel between medium and long distances (150 and 1,200 km), HSR has an increasing role in intercity travel worldwide. Decision makers, transportation planners, system designers, and operators as well as political leaders need to understand HSR's operational boundaries for intercity travel to determine which HSR will outperform the others and under which conditions. The analysis uses a simple time-distance factor to clarify the dominance. To confirm the validity of HSR in intercity passenger rail services, a comparison with the external competition of car and air travel is necessary. Meanwhile, an internal examination of operational performance considering sophisticated variables is imperative. The dissection, based on numerous HSR projects, selects four interrelated trade-off elements: the passenger access time and travel time associated with the total on-line travel time, the area coverage associated with the station density, the station density associated with speed, and the transit unit (TU) size, frequency, and loading factor associated with the independent line capacity. After examining the interrelations and trade-offs, a practical case study presents one of the major US economic corridors - the Northeast Corridor. The case study explores the geospatial metadata and concludes that three major system efficiency challenges exist; therefore, it provides corresponding engineering measures to convert an independent dead-end terminal into an integrated through-running station, which are the priority for converting Amtrak, the US national rail service, into an accelerated HSR service. It is time to renew the government's interest in paying systematic attention to the comprehensive effect of HSR.
Keywords: L92; R41; R53; 330; high-speed rail; regional connectivity; comprehensive effect; system performance; operational measure